Circulating SARS-CoV-2 spike IgG antibody responses in cancer patients following multiple COVID-19 vaccination boosters - Xue, Huijing; Kemp, Troy J.; North, Hayley; Roche, Nancy V.; Hickey, Thomas E.; Pinto, Ligia A. (Frontiers in Immunology, 2025)
IntroductionIndividuals with cancer have a higher risk of SARS-CoV-2 infection, severe disease, hospitalization and death compared to healthy individuals. Understanding the immune response to different doses of COVID-19 vaccines in this population is essential to inform vaccine recommendations. This study aimed to compare the post-vaccination humoral immune response of people with cancer versus healthy participants via assessment of anti-spike IgG antibody levels and avidity 1 month and 6 months post-last vaccination. MethodsCirculating anti-spike IgG levels and antibody avidity were measured in sera from cancer and healthy cohorts using ELISA and chaotropic-based avidity assays.ResultsIn general, individuals with hematological cancers showed significantly lower antibody levels and avidity across two-, three- and four-doses compared to healthy individuals. Additionally, individuals with hematological cancers who received two doses of vaccine exhibited a significantly slower avidity development at both time points compared to healthy individuals. In contrast, individuals with solid cancers exhibited similar antibody levels and avidity compared to healthy participants. Factors including age, sex and vaccine received also influenced immune responses. DiscussionThese findings suggest the need for customized vaccination strategies for vulnerable populations.